Therapy of acute myeloid leukemia: therapeutic targeting of tyrosine kinases. (3rd April 2019) - Cioccio, Joseph; Claxton, David
ABSTRACT: Introduction : Tyrosine kinases (TKs) drive cell survival and proliferation in many normal and malignant cell types. TKs are frequently mutated in acute myeloid leukemia (AML) and hence are increasingly targeted. The management of AML has dramatically improved because of TKI-targeted treatment. Areas Covered : This review provides a biological background for TK inhibitors (TKIs) in AML and reviews their use in the clinic. TK expression and mutation in AML are explored with a focus on TKs associated with specific AML subsets and treatment outcomes. TKIs that specifically target FLT3, c-Kit, and Jak2 are discussed. TKI targeting of specific genes mutated in individual cases and general 'untargeted' use of these agents are highlighted. Lastly, the mechanisms TKI drug resistance in AML are explored. Expert Opinion : The use of TKIs in the clinic is improving outcomes for many patients. An improved understanding of tyrosine kinase biology and the expanding use of TKIs are likely to dramatically improve outcomes in the coming decade. TKIs and other targeted agents could gradually supplant the use of cytotoxic chemotherapy for AML.